PENGARUH HASIL GRADASI AGREGAT KELAS B TERHADAP KEPADATAN LAPANGAN PADA RUAS JALAN SIMPANG BENTUAS – SIMPANG MUARA JAWA - KIR, SYA (KURVA S JURNAL MAHASISWA, 2014)
Granules pavement is a construction is built on the foundation soil layer (sub grade), which serves to bear the weight of traffic. Aggregate Base is the foundation layer is the main ingredient composed of granular aggregate or stone material. Aggregates are granular materials are hard and compact and is the aggregate may include cobblestone, crushed stone, stone dust and sand. In addition to the base course, the aggregate has a very important role in the transport infrastructure, particularly in this case the pavement. Carrying capacity of the road pavement is determined largely by the characteristics of the aggregates used.Bentuas road intersection mouth of Java is a road that will connect with the road axis, toward the mouth of the districts and sub-districts of Java Samboja, so the road construction is carried out in order to facilitate access to traffic. The method used for data collection is a method of testing the field with a cone of sand and a method of sieving or distribution of grain in the laboratory.From the results of calculations can be concluded that, sieving or grading tests performed in the laboratory as many as 13 samples. Sieve analysis test should not exceed 2% out of the ring boundary gradation in order to achieve maximum density, if in excess of 2% will be increased compaction trajectory. While the field density testing as many as 40 samples from the site grade B aggregate densty testing in the field. Field density testing results meet the technical specifications (> 98.00%), with an average percentage of density is 101.61%.